Teacher’s Perception of the Digital Report Card Application and it’s Implementation at Private Primary School for Islamic Studies - Fatkhur Rohman; Candra Wijaya; Anri Naldi (IAIN Padangsidimpuan, 2021)
Since the scrolling of the Handbill of the Directorate General of Islamic Education, Ministry of Religion Affair Number: 1594/DJ.I/DT.II.I/KS.00/10/2018, date October 29, 2018 about Digital Report Card Application use, Digital Report Card Application for Primary School for Islamic Studies enforced to public and private Primary School for Islamic Studies throughout Indonesia. This research is the result of a field study, which aims to analyze teachers' perceptions about the digital report card application and its implementation at Elsusi Meldina Private Islamic Boarding School. The research data, obtained through observation, interviews, and document study, then analyzed using the Miles and Hubermen analysis model. This study found that teachers' perceptions that the digital report card application are a substitute application for manual report cards that are run using a computer (laptop) and an Excel program that uses an online-based application whose purpose is to assess student learning outcomes, and facilitate teacher performance in working on student learning outcomes. The implementation of the Digital Report Card application is carried out based on Standard Operating Procedures (SOP) in accordance with the Circular of the Ministry of Religion Affair of the Indonesia Republic